Fruits, vegetables, and health: A comprehensive narrative, umbrella review of the science and recommendations for enhanced public policy to improve intake - Wallace, Taylor C.; Bailey, Regan L.; Blumberg, Jeffrey B.; Burton-Freeman, Britt; Chen, C-y. Oliver; Crowe-White, Kristi M.; Drewnowski, Adam; Hooshmand, Shirin; Johnson, Elizabeth; Lewis, Richard; Murray, Robert; Shapses, Sue A.; et al. (Critical reviews in food science and nutrition, 2020)
Fruit and vegetables (F&V) have been a cornerstone of healthy dietary recommendations; the 2015-2020 U.S. Dietary Guidelines for Americans recommend that F&V constitute one-half of the plate at each meal. F&V include a diverse collection of plant foods that vary in their energy, nutrient, and dietary bioactive contents. F&V have potential health-promoting effects beyond providing basic nutrition needs in humans, including their role in reducing inflammation and their potential preventive effects on various chronic disease states leading to decreases in years lost due to premature mortality and years lived with disability/morbidity. Current global intakes of F&V are well below recommendations. Given the importance of F&V for health, public policies that promote dietary interventions to help increase F&V intake are warranted. This externally commissioned expert comprehensive narrative, umbrella review summarizes up-to-date clinical and observational evidence on current intakes of F&V, discusses the available evidence on the potential health benefits of F&V, and offers implementation strategies to help ensure that public health messaging is reflective of current science. This review demonstrates that F&V provide benefits beyond helping to achieve basic nutrient requirements in humans. The scientific evidence for providing public health recommendations to increase F&V consumption for prevention of disease is strong. Current evidence suggests that F&V have the strongest effects in relation to prevention of CVDs, noting a nonlinear threshold effect of 800 g per day (i.e., about 5 servings a day). A growing body of clinical evidence (mostly small RCTs) demonstrates effects of specific F&V on certain chronic disease states; however, more research on the role of individual F&V for specific disease prevention strategies is still needed in many areas. Data from the systematic reviews and mostly observational studies cited in this report also support intake of certain types of F&V, particularly cruciferous vegetables, dark-green leafy vegetables, citrus fruits, and dark-colored berries, which have superior effects on biomarkers, surrogate endpoints, and outcomes of chronic disease.